Identification of Anti-Cancer Compounds in Medicinal Plants Using Metabolomic Approaches: A Review - Magfiroh, Yani (Bioeksperimen: Jurnal Penelitian Biologi, 2023)
The modern lifestyle despite its comfort has made cancer a second leading public health problem, following cardiovascular disease. As chemotherapeutic has many side effects including resistance, recent attention has focused on plants which may provide a good opportunity for complementary cancer treatment. Several studies have begun to focus on metabolomic research in order to discover the mechanisms of action of diverse medicinal plants, investigate biomarkers, and comprehend cancer progression at metabolic rates. This study aims to analyze and highlight related metabolomic investigations in medicinal plants that demonstrate the potential of biomarker compounds and their processes in cancer disease. The research methodology uses a literature review that is compiled from many connected journals. According to the findings, bioactive substances present in medicinal plants can be used as biomarkers to disrupt the metabolism of enzymes, transporters, and signaling pathways in cancer cells. Utilized analytical platforms include HPLC, GC-MS, FTIR and NMR. Statistical analysis employs the Anova, PCA, and OPLS-DA methods. Finally, we reviewed biomarkers of medicinal plants and metabolomic pathways, with the result that anticancer compounds may exert their activity by various methods affecting DNA replication, cell cycle, migration and apoptosis.